Cardiovascular Prognosis in Drug-Resistant Hypertension Stratified by 24-Hour Ambulatory Blood Pressure: The JAMP Study. Issue 6 (1st November 2021) - Kario, Kazuomi; Hoshide, Satoshi; Narita, Keisuke; Okawara, Yukie; Kanegae, Hiroshi
Abstract : Supplemental Digital Content is available in the text. Abstract : Resistant hypertension is an important cardiovascular risk factor. This analysis of the JAMP study (Japan Ambulatory Blood Pressure Monitoring Prospective) data investigated the effects of uncontrolled resistant hypertension diagnosed using ambulatory blood pressure (BP) monitoring on the risk of heart failure (HF) and overall cardiovascular events. The JAMP study patients with hypertension and no HF history were included. They had true resistant hypertension (24-hour BP ≥130/80 mm Hg), pseudoresistant hypertension (24-hour BP <130/80 mm Hg), well-controlled nonresistant hypertension (24-hour BP <130/80 mm Hg), or uncontrolled nonresistant hypertension (24-hour BP ≥130/80 mm Hg). The primary end point was total cardiovascular events, including atherosclerotic cardiovascular disease (fatal/nonfatal stroke and fatal/nonfatal coronary artery disease), and HF. During 4.5±2.4 years of follow-up the overall incidence per 1000 person-years was 10.1 for total cardiovascular disease, 4.1 for stroke, 3.5 for coronary artery disease, and 2.6 for HF. The adjusted risk of total cardiovascular and HF events was significantly increased in patients with true resistant versus controlled nonresistant hypertension (hazard ratio, 1.66 [95% CI, 1.12–2.48]; P =0.012 and 2.24 [95% CI, 1.17–4.30]; P =0.015, respectively) and versus uncontrolled nonresistant hypertension (1.51 [1.03–2.20]; P =0.034 and 3.03 [1.58–5.83]; P <0.001, respectively). The findings were robust in a sensitivity analysis using a slightly different definition of resistant hypertension. True resistant hypertension diagnosed using ambulatory BP monitoring is a significant independent risk factor for cardiovascular disease events, especially for HF. This highlights the importance of diagnosing and effectively treating resistant hypertension. Registration: URL: https://www.umin.ac.jp/ctr ; Unique identifier: UMIN000020377.